Analisis Pendapatan Usahatani Padi Sawah dan Sayuran di Desa Dawi-Dawi Kecamatan Wonggeduku Kabupaten Konawe - Dermawansa, Dermawansa; Buana, Tjandra; Zani, Munirwan (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2017)
This research aims to find out Paddy and vegetable farm income, and Paddy and vegetable farm efficiency in Dawi-Dawi Village, Wonggeduku Subdistrict, Konawe Regency. The population of this research is comprised of all farmers who grow paddy and plant vegetables (tomato and yardlong bean) in Dawi-Dawi Village, Wonggeduku Subdistrict, Konawe Regency which consist of 21 farmers. Samples are taken using census method, in which all of the population is taken as research sample. Therefore, a number of samples in this research are 21 farmers. The data are analyzed using income analysis, namely, Pd = TR TC and farm efficiency analysis R/C Ratio = TR/TC. The results show that: (1) paddy farm incomes per season range from IDR 1,901,250 – IDR 24,492,250 with the average of IDR 7,697,670. Tomato farm incomes per season range from IDR 1,979,772 – IDR 25,351,820 with an average of IDR 7,970,189. Yardlong bean farm incomes per season range from IDR 1,532,389 – IDR 3,391,000 with an average of IDR 1,822,370, and (2) Paddy, tomato and yardlong bean farms are deemed efficient with the R/C ratio of 2.73, 2.97, and 3.13 respectively.